Calcium chloride combined with dimethyl sulphoxide for the chemical sterilization of dogs - Silva, Renata C. A.; Paranzini, Cristiane S. [UNESP]; Franco, Leandro G.; Miguel, Marina P.; Honsho, Cristiane S.; Souza, Fabiana F. [UNESP] (Wiley, 2018)
The aim of this study was to evaluate the effect of intratesticular injection of calcium chloride (CaCl2) combined with dimethyl sulphoxide (DMSO) as a chemical sterilization in dogs. Twelve dogs were divided into two groups: the treated group (n = 6), in which 15 mg/kg of a 7.5% CaCl2 solution combined with 0.5% DMSO was injected into each testicle (volume range 1.0-4.76 ml); and a control group (n = 6) that received the same volume/kg of 0.9% sodium chloride solution (NaCl). Semen characteristics pre- and post-treatment were evaluated. Serum testosterone concentration was determined before the injection (D-1) and at 15 (D15), 30 (D30) and 60 (D60) days after intratesticular injection. Testicle sizes and local pain were evaluated for 7 consecutive days (D1 to D7) and at D15, D30 and D60 after injection. At D60, testicle histological evaluation was performed after orchiectomy. No pain was observed by testicular palpation, with the exception of one dog in the treated group; this dog then received analgesic therapy. An increase in testicular volume was evident within 24 hr after treatment, followed by gradual reduction for 3 weeks. Five of 6 dogs from the treated group presented azoospermia at D15; the remaining dog presented at D30. There was no significant difference in testosterone concentrations in the treated group during the experimental period. Histological evaluation showed testicular degenerative lesions, especially at the proximal and middle portions. The results indicated that one injection of 7.5% CaCl2 combined with 0.5% DMSO into each testis is a viable alternative for canine sterilization.
Keywords: azoospermia; canine; chemical-castration; pain; testicle